Estudo da exposição pessoal ao material particulado atmosférico em Londrina - Almeida, Daniela Sanches de (2016)
The exposure to air pollutants in humans causes damage effects on health. Urban areas with high population density and high vehicular flows are critical regions. Air pollutants are omnipresent, and some level of exposure is inevitable, variable and dependent on a number of environmental and individual factors of each. This work aimed to measure and assess personal exposure to airborne particulate matter by individuals in Londrina with 30 voluntaries from 6 occupation classes. Using personal monitors the concentration of airborne particulate matter concentrations were measured in mass and number of particles in the inhaled air. Buccal cells of the volunteers were collected before and after exposure to the determination of genotoxicity by Comet assay. Sampling campaigns were carried out in winter with georeferenced routes that varied according to the routine of each individual. From concentrations measured, time of exposure and body weight the received doses were calculated individually. The mass concentrations (average of 8 hours) found in the volunteers ranged from 2.41 to 34.07 µg m-3 for MP1,0 and 23.11 to 11060.54 µg m-3 for PM10. The concentrations in number of particles found varied from 14 to 183 particles cm-3 to MP0,3; for PM2.5 they varied from 0.20 to 27 particles cm-3. Construction and Industry category showed the highest doses, while the administrative sector had the lowest. Using the Kruskal Wallis test was found a significant difference of DNA damage in classes Trade, Construction and Industry and Transportation, when these were compared with the control group (Administrative class). The model best suited to the data was the Negative Binomial, indicating positive association, mainly of the occupation class, number of particles with damage to DNA from buccal cells. The results of the lung deposition simulation from the concentrations obtained in the sample show that in volunteers where the predominant particle diameter was smaller, the fraction deposited in the lungs was higher, although the bulk concentration was higher. The results show the importance of particle size and chemical composition on the health effects, the importance of personal exposure measurements for epidemiological studies on health and the feasibility of this type of personal sampling, but for more significant results it is recommended the magnification of this study.